IMPLEMENTASI ALGORITME A-STAR UNTUK PEMETAAN KOORDINAT TUMBUHAN LANGKA BERBASIS WEB - Fauzi, Ahmad; ,, Supriyadi; Yanitasari, Yessy (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2018)
The path finding optimization is the most widely discussed issues in the informatics scope. This was related to the increased needs of the transportation, distribution and industry. The method for solving search problems for the shortest path can be done using two methods, namely the conventional method and the heuristic method. The conventional method uses a mathematical approach that is easy to understand, but the search results require a relatively long time. In order for search time to be faster, a heuristic approach is needed, although it requires more parameters. A-star algorithm is a heuristic route search method that is very effective in finding the shortest route. In this study a web-based application was developed by integrating the A-star algorithm to find the location of rare plants in the conservation area. As for determining the distance between the coordinates of the plant using haversine formula. This application is very important because of the large number of plants and the limited guidance of researchers in finding the location of rare plants in conservation areas. The guide is presented in the form of an easy-to-understand graph accompanied by information about the plants sought.